Annotated checklist of Orthoptera from Kazimzumbwi Forest Reserve, Tanzania with the description of new species and discussion of the biogeographic patterns of threatened species - Hemp, Claudia (Zootaxa, 2017)
A checklist of Ensifera and Acridomorpha of Kazimzumbwi Forest Reserve, Kisarawe near Dar es Salaam is given and eight new Tettigoniidae species described. These are the Agraeciini species Afroagraecia kisarawe n. sp., the Meconematinae species Phlugidia kisarawe n. sp., and the female of Aerotegmina megaloptera (Hexacentrinae). The Phaneropterinae species Dioncomena scutellata n. sp. is known at present only from two localities, the Pugu Hills near Dar es Salaam and Kwamgumi forest reseve on the foothills of the East Usambara Mountains. Two new Eurycorypha species, E. annexata n. sp. and E. ligata n. sp. are described from the area known at present only from the male sex. A second species is described in the genus Lunidia Hemp, L. acuticercata n. sp. Two new Phaneropterinae genera are erected on Pseudopreussia flavifolia n. gen. n. sp. and Materuana ericki n. gen. n. sp., species of wet lowland forest along coastal Tanzania and forest reserves in the East Usambara and on the foothills of the Uluguru Mountains.Kazimzumbwi Forest Reserve is severly threatened by encroachment and deforestation although it is recognized as belonging to the oldest surviving forests of the world.